Effect of Partial Replacement of Kaolin with Waste Sanitary Ware in the Production of Ceramic Socket - Ologunwa, Temitope Peter; Hossanah, Clement (Diponegoro University, 2024)
The research investigates the utilization of waste materials from recycled sanitary ware in the manufacture of ceramic sockets. The debris is often thrown away in surroundings of building and land fills. However, they can be recycled to provide sustainable solution to the melting problems on wall plugs. In order to create the right ceramic materials for the research, raw materials like kaolin, ball clay, and feldspar are extracted from old ceramic sinks, toilets, and bathtubs. The research's goal is to use processed ceramic materials to address the melting problem with wall sockets. Additionally, it uses an experimental procedure to create ceramic sockets from waste sanitary ware and other materials. The materials are processed, mixed, pressed, dried, and fired to achieved the desirable result. Sanitary ware waste was used to replace kaolin at intervals of 5% variation. According to the outcomes of the tests, adding recycled sanitary waste to ceramic sockets enhances their physical, mechanical, and dielectric strength. The addition of sanitary ware waste has increased the dielectric strength property, compressive strength results as also shown the strength of sanitary ware wastes compare to that of kaolin. The findings have shed light on the viability and possibility of employing recycled sanitary ware waste products in the manufacture of ceramic sockets. It also meets up to the British Standard for plug and socket BS 1363, which has the ability to withstand high and low temperature for both residential uses 120-240v and industrial usages. The sample produced pass the least dieletric strength for any insulator at 3kΩ/mm resulting into a mega ohm (mΩ).